Towards the development of a strategy for a national spatial data infrastructure - Al-Shahrani, Abdullah M.R. (2002)
In today's world of ever advancing technology the time is precisely right for investment in the development and implementation of a national spatial data infrastructure. This implies that all spatial data presently scattered in different departments and organisations are coordinated and shared. In the Kingdom of Saudi Arabia there are a number of different mapping and Geographic Information System (GIS) activities being implemented within various government organisations, each with its own merits. Certain research and pilot projects have also been carried out aiming to provide help and recommendations with regard to spatial data sharing and to promote awareness of the importance of spatial data to the Kingdom's development. However, there is an urgent need for a consolidation of effort to avoid the costly mistake of duplication of work; hence the need for a unified national spatial data infrastructure.